Growth in early life predicts bone strength in late adulthood: the Hertfordshire Cohort Study. - Oliver, H; Jameson, K; Sayer, A; Cooper, C; Dennison, E (2007)
Infant growth is a determinant of adult bone mass, and poor childhood growth is a risk factor for adult hip fracture. Peripheral quantitative computed tomography (pQCT) allows non-invasive assessment of bone strength. We utilised this technology to examine relationships between growth in early life and bone strength. We studied 313 men and 318 women born in Hertfordshire between 1931 and 1939 who were still resident there in adult life, for whom detailed early life records were available. Lifestyle factors were evaluated by questionnaire, anthropometric measurements made, and peripheral QCT examination of the radius and tibia performed (Stratec 4500). Birthweight and conditional weight at 1 year were strongly related to radial and tibial length in both sexes (p<0.001) and to measures of bone strength [fracture load X, fracture load Y, polar strength strain index (SSI)] at both the radius and tibia. These relationships were robust to adjustment for age, body mass index (BMI), social class, cigarette and alcohol consumption, physical activity, dietary calcium intake, HRT use, and menopausal status in women. Among men, BMI was strongly positively associated with radial (r=0.46, p=0.001) and tibial (r=0.24, p=0.006) trabecular bone mineral density (BMD). Current smoking was associated with lower cortical (radius: p=0.0002; tibia: p=0.08) and trabecular BMD (radius: p=0.08; tibia: p=0.04) in males. Similar trends of BMD with these anthropometric and lifestyle variables were seen in women but they were non-significant. Current HRT use was associated with greater female cortical (radius: p=0.0002; tibia: p=0.001) and trabecular (radius: p=0.008; tibia: p=0.04) BMD. Current HRT use was also associated with greater radial strength (polar SSI: p=0.006; fracture load X: p=0.005; fracture load Y: p=0.02) in women. Women who had sustained any fracture since the age of 45 years had lower radial total (p=0.0001), cortical (p<0.005) and trabecular (p=0.0002) BMD, poorer forearm bone strength [polar SSI (p=0.006), fracture load X and Y (p=0.02)], and lower tibial total (p<0.001), cortical (p=0.008), and trabecular (p=0.0001) BMD. We have shown that growth in early life is associated with bone size and strength in a UK population aged 65-73 years. Lifestyle factors were associated with volumetric bone density in this population.